SPRITUALITAS PENDIDIK PENGARUHNYA TERHADAP KARAKTER ANAK DI SEKOLAH DASAR ISLAM TERPADU BANDA ACEH - Ainal Mardhiah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
This study examines the character of educators and their influence on the character of students in the Banda Aceh Integrated Islamic School (SDIT). This study uses a simple regression statistical test with the formula Y = a + bX for 7 teachers and 58 students in grade 6 SDIT Nurul Ishlah Banda Aceh. Data were collected through observation, questionnaires, and interviews based on the scale of spiritual intelligence and character scale of children. Data analysis using regression and correlation techniques. The results of the regression analysis showed a significant positive relationship between spiritual intelligence and the character of students. Similarly, the results of the analysis of the correlation of spiritual intelligence with the character of students showed a significant positive relationship. With the correlation value r = 0.38 and Y = 38.215 + 0.340x. So, the results of the study concluded that the more religious the character of the educator the better the character of the child. The findings of this study are different from the findings of Danah Zohar and Ian Marsal (2007) which state that educator's spirituality is not related to the religion and religious beliefs that one believes. However, research supports the findings of Muhammad Djarot Sensa (2004) who said that this spiritual relationship is religious.